Evolution of Microfinance and Its Relevance in Nepal - Gautam, Jagannath (International Research Journal of Parroha, 2023)
This research paper seeks to explore the evolution of microfinance in Nepal and its potential contributions to the nation's inclusive growth. This study employs a comprehensive and interdisciplinary approach, incorporating data from various sources, including government reports, academic research, and field observations. The research uncovers the historical development of microfinance in Nepal, tracing its roots from early government initiatives to the emergence of non-governmental organizations and international models. The paper also presents case studies showcasing the impact of microfinance on poverty reduction, women's empowerment, and financial inclusion in rural and urban areas. Challenges such as interest rates, regulatory frameworks, and accessibility are discussed in detail. Furthermore, the study explores the future prospects of microfinance in Nepal, emphasizing the role of technological innovations and financial product diversification. This research paper provides a comprehensive analysis of the relevance of microfinance in Nepal, shedding light on its historical evolution, impact on poverty reduction, challenges, and future prospects. It highlights the critical role microfinance plays in providing financial services to marginalized populations in a diverse and geographically challenging nation. The paper concludes by underlining the continued importance of microfinance in Nepal's socio-economic development and the need for innovative solutions to address the challenges it faces.